Timing of College Enrollment and Family Formation Decisions - Maria Knoth Humlum; Jannie H. G. Kristoffersen; Rune Majlund Vejlin (Institute for the Study of Labor (IZA), 2014)
The level of progression of an individual's educational or labor market career is a potentially important factor for family formation decisions. We address this issue by considering the effects of a particular college admission system on family formation. We show that the admission system affects mainly the timing of college enrollment and not the college-going decision. As such, we consider a specific type of career interruption and its consequences for relationship formation and fertility decisions. Specifically, we employ a regression discontinuity design based on the college admission system to estimate the effect of being above the admission requirement in the year of application on later family formation decisions. We find that the admission system has substantial effects on the timing of family formation and, specifically, that the timing of college enrollment is an important determinant hereof. This suggests that career interruptions such as delays in the educational system can have large effects on family decision-making.
Keywords: I2; J12; J13; 330; fertility; education policy; career interruptions; delayed college enrollment; regression discontinuity